Pemanfaatan Teknologi OCR dan JWT Authentication dalam Pengembangan Aplikasi Pencatatan Aset Multi-Platform Berbasis Flutter - Agus Syuhada; T. Yudi Hadiwandra; Rayhan Al Farassy (LPPM Universitas Potensi Utama, 2026)
Conventional asset management in the IT Division of PT Pertamina Hulu Rokan (PHR) causes data redundancy, manual errors, and slow validation. This study aims to build a multi-platform asset management application to improve recording effectiveness. The system integrates Optical Character Recognition (OCR) for faster asset label identification and Role-Based Access Control (RBAC) for security. Quality testing utilized the ISO/IEC 25010 standard and experimental testing. Results show the application successfully bridges operational needs via a mobile platform (Android) for Field Officers and a desktop platform (Windows) for Admins. ISO/IEC 25010 testing confirmed all main functionalities work validly. Experimental testing proved the application significantly reduces data redundancy and human errors. In conclusion, this multi-platform architecture effectively creates a centralized, accurate, flexible, and real-time asset management ecosystem, outperforming conventional methods.